ANALYSIS OF SATISFACTION LEVEL AND NET BENEFIT IPB UNDERGRADUATE STUDENTS TOWARDS THE USE IPB MOBILE FOR STUDENT APPLICATION - Frista Shabila; Moh. Djemdjem Djamaludin (Journal of Child, Family, and Consumer Studies, 2022)
IPB University implements a mobile-based management information system through the IPB Mobile for Student application to bring technological innovation closer and realize transformation into a digital campus. This study aims to analyze the perception of quality, level of satisfaction and net benefit felt by S1 IPB students towards the IPB Mobile for Student application. This research is a quantitative research using explanatory design. This research was conducted on IPB students using voluntary sampling techniques so that 306 respondents were obtained. Data is collected through tools in the form of questionnaires that are distributed online using google forms. The data obtained were processed using Microsoft Excel, SPSS version 25, and SEM-LISREL 8.80. The results of the influence test showed a positive and significant influence on the perception of quality on user satisfaction and user satisfaction had a significant positive effect on net benefits. The advice that can be given is that users are expected to provide input on the shortcomings in the application so that IPB University as an application developer can improve the quality of the IPB Mobile for Student application.